Androgens and cardiovascular disease in postmenopausal women: a systematic review. (December 2014) - Spoletini, I.; Vitale, C.; Pelliccia, F.; Fossati, C.; Rosano, G. M. C.
Abstract Androgens play a pivotal role in cardiovascular function and their effects differ between men and women. In postmenopausal women, testosterone replacement within physiological levels is associated with overall well-being. However, a definitive explanation as to how androgens have an impact on cardiovascular health in postmenopausal women and whether they may be used for cardiovascular treatment has yet to be established. With these aims, a systematic review of the existing studies on the link between androgens and cardiovascular disease and the effects of testosterone therapy on cardiovascular outcomes in postmenopausal women has been conducted. The few existing studies on cardiovascular outcomes in postmenopausal women indicate no effect or a deleterious effect of increasing androgens and increased cardiovascular risk. However, there is evidence of a favorable effect of androgens on surrogate cardiovascular markers in postmenopausal women, such as high density lipoprotein cholesterol, total cholesterol, body fat mass and triglycerides. Further studies are therefore needed to clarify the impact of therapy with androgens on cardiovascular health in postmenopausal women. The cardiovascular effect of testosterone or methyltestosterone with or without concomitant estrogens needs to be elucidated.